Exploring the complexities of crafting new normality through collaborative situated resilience practices between high-containment laboratories and communities - Barnhart, David Patrick (My University, 2025)
This dissertation develops Resilience-as-Practice (RAP) as a theoretical and analytical framework for understanding how resilience is co-constructed between high-containment laboratories and community stakeholders. Situated within a processual ontology and grounded in Leadership-as-Practice, the Communicative Theory of Resilience, and the Communicative Constitution of Organizations, RAP conceptualizes resilience as a socio-material, communicative accomplishment emergent through everyday organizing. Central to this framework is the concept of the resilience episode, defined as a situated, empirical unit of analysis that marks a trajectory shift toward a collaboratively produced “new normal.” Using a single instrumental case study of the National Bio-Agro Defense Facility in Manhattan, Kansas, this research examines how resilience practices are enacted in situ through communicative and material resources. Guided by phronetic iterative qualitative data analysis, the study draws on interviews and field observations to answer two research questions: (1) How are resilience practice(s) co-constructed between high-containment labs and community stakeholders to overcome barriers to building community trust? and (2) What factors prevent co-action spaces from solidifying and producing resilience, particularly in building trust between high-containment labs and communities? Findings identify five enabling practices, organizing around experiential engagement, strategic facilitation, calibrated transparency, priority convergence, and diverse communication, and five constraining factors, including limited resources, operational constraints, language intimidation, conflicting matters of concern, and lingering fears and rumors. The study contributes to resilience and leadership scholarship by offering a practice-based ontology of resilience, emphasizing hybrid agency and emergent organizing.
Keywords: Resilience; Resilience-as-Practice; Resilience episodes